1998
DOI: 10.1002/(sici)1097-0215(19980717)77:2<188::aid-ijc3>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of level of circulating abnormal lymphocytes among human T-lymphotropic virus type I carriers in Japan

Abstract: Human T‐lymphotropic virus type I (HTLV‐I) carriers often have abnormal lymphocytes (Ably) that resemble malignant cells of adult T‐cell leukemia (ATL). To identify predictors of the level of Ably in a longitudinal study of asymptomatic HTLV‐I carriers, we analyzed data from 215 subjects (67 men and 148 women) with multiple Ably measurements on blood smears. Ably+ (those having Ably > 0.6% of leukocytes counted on a blood smear at least once) was strongly associated with a high proviral<0B> <0R>load (OR 8.9; 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 16 publications
1
23
0
1
Order By: Relevance
“…Tax3 purified protein was then used as an antigen to detect anti-Tax3 antibodies in serial dilutions of the serum obtained from the previously described HTLV-3-infected individual (Pyl43) (Calattini et al, 2005), as well as in the sera from several African monkeys. Such a technique has previously been used for detecting anti-Tax1-specific antibodies among HTLV-1-infected patients (Coates et al, 1990;Chen et al, 1997;Hisada et al, 1998). Using a sensitive PCR technique with HTLV-1-and HTLV-2-specific PCR primers, we previously demonstrated that neither the individual infected with HTLV-3 nor the monkeys infected with STLV-3 were also co-infected with HTLV-1/STLV-1 or HTLV-2/STLV-2 Calattini et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Tax3 purified protein was then used as an antigen to detect anti-Tax3 antibodies in serial dilutions of the serum obtained from the previously described HTLV-3-infected individual (Pyl43) (Calattini et al, 2005), as well as in the sera from several African monkeys. Such a technique has previously been used for detecting anti-Tax1-specific antibodies among HTLV-1-infected patients (Coates et al, 1990;Chen et al, 1997;Hisada et al, 1998). Using a sensitive PCR technique with HTLV-1-and HTLV-2-specific PCR primers, we previously demonstrated that neither the individual infected with HTLV-3 nor the monkeys infected with STLV-3 were also co-infected with HTLV-1/STLV-1 or HTLV-2/STLV-2 Calattini et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The first possibility is that the dose of the green tea extract powder used in this study (9 capsules of "Nanchariki") is insufficient for suppression of HTLV-1 carriers' lymphocytes in vivo, since the concentration of EGCg in plasma is estimated to be about 0.3 µg/ml, 27) which is far less than the range of 3-27 µg/ml required to inhibit the growth of HTLV-1-infected T-cells in vitro. 22) The second is that the majority of the HTLV-1 carriers are females, who may have fewer abnormal lymphocytes in the circulation than males 28,29) and their HTLV-1-infected lymphocytes may be less sensitive to apoptosis induction by green tea components. 22) The third is that individual variation in absorption and metabolism of tea polyphenols 30) may produce heterogeneous responses in diminution of HTLV-1 provirus load, so that it is difficult to obtain a consistent result with statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with a higher provirus load, who are at risk for ATL, may derive particular benefit from green tea drinking because they have increased number of abnormal lymphocytes that are prone to apoptosis. 22,29,33) "Nanchariki" is made of whole extract of green tea, which contains caffeine and polyphenol compounds. Decaffeinated capsules of green tea extract powder may minimize in the effects on the stomach and bowel movements encountered in the drop-out cases in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study of HTLV-Iinfected individuals identified carriers who later developed ATL, showed that the anti-Tax level was low in all ATL cases for up to 10 years preceding their diagnosis, independent of the level of anti-HTLV-I titer. This finding indicates that HTLV-I carriers with a higher anti-HTLV-I titer and a lower anti-Tax reactivity may be at greatest risk of ATL (Hisada et al, 1998). The levels of anti-HTLV-I antibody and soluble IL-2 receptor (sIL-2R) have been shown to be correlated with HTLV-I provirus load (Etoh et al, 1999), and high antibody titers, and high sIL-2R were risk factors to develop ATL among carriers (Arisawa et al, 2002).…”
Section: Immunodeficiency and Development Of Atlmentioning
confidence: 98%